Further examination of the treatment of multiply controlled inappropriate mealtime behavior. Issue 1 (13th July 2020) - Kirkwood, Caitlin A.; Bachmeyer‐Lee, Melanie H.; Sheehan, Connor M.; Mauzy, Courtney R.; Gibson, Logan A.
Abstract : We systematically replicated Bachmeyer et al. (2009) by examining extinction procedures matched to each function, individually and in combination, to treat the food or liquid refusal of 4 children diagnosed with a feeding disorder whose inappropriate mealtime behavior was maintained by multiple functions (i.e., escape and attention). Previous research suggests that adding differential reinforcement to extinction procedures may result in better treatment outcomes. Therefore, we added differential reinforcement to extinction procedures matched to each function. Differential reinforcement and extinction matched only to escape or attention resulted in low rates of inappropriate mealtime behavior and high, stable levels of acceptance for only 1 child. Consistent with Bachmeyer et al., inappropriate mealtime behavior decreased, and acceptance increased for the remaining 3 children only after we matched differential reinforcement and extinction procedures to both escape and attention.